2010
DOI: 10.1007/s11665-010-9768-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Superheat on Microstructure and Mechanical Properties of Ductile Cu47.5Zr47.5Al5 Bulk Metallic Glass-Matrix Composite

Abstract: Generally bulk metallic glasses (BMGs) posses very less ductility and toughness at room temperature. Over the recent past years to improve up on these properties in many alloy system BMG composites have been developed. It was also reported that Cu 47.5 Zr 47.5 Al 5 BMG composite shows a very high strength together with an extensive work hardening-like behavior of large ductility around 18%. In this study, the influence of superheat on microstructure and the resulting mechanical properties in Cu 47.5 Zr 47.5 Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The final state of the cast rod depends on a number of factors, including casting temperature T cast , mold temperature T mold , rod diameter, thermal conductivity and thickness of the mold material, and the heat transfer coefficient between the cast rod and the mold. For the same Zr-based composition, it was confirmed that the formation of a number of eutectoid phases or a fully amorphous structure depends only on T cast . In our case, increasing T cast leads to the formation of two martensitic CuZr phases ( Cm and P 2 1 / m ) and CuZr 2 crystals in rods of 2 and 3 mm diameter (Figure S6).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The final state of the cast rod depends on a number of factors, including casting temperature T cast , mold temperature T mold , rod diameter, thermal conductivity and thickness of the mold material, and the heat transfer coefficient between the cast rod and the mold. For the same Zr-based composition, it was confirmed that the formation of a number of eutectoid phases or a fully amorphous structure depends only on T cast . In our case, increasing T cast leads to the formation of two martensitic CuZr phases ( Cm and P 2 1 / m ) and CuZr 2 crystals in rods of 2 and 3 mm diameter (Figure S6).…”
Section: Discussionsupporting
confidence: 55%
“…28−30 For the same Zr-based composition, it was confirmed that the formation of a number of eutectoid phases or a fully amorphous structure depends only on T cast . 31 In our case, increasing T cast leads to the formation of two martensitic CuZr phases (Cm and P2 1 /m) and CuZr 2 crystals in rods of 2 and 3 mm diameter (Figure S6). Thus, glassy phase separation may be useful in controlling the length scales also in crystalline or partially crystalline microstructures.…”
Section: Discussionmentioning
confidence: 55%